Obesity during childhood is associated with higher cancer mortality rate during adulthood: the i3C Consortium - Nuotio Joel; Laitinen Tomi T.; Sinaiko Alan R.; Woo Jessica G.; Urbina Elaine M.; Jacobs David R. Jr.; Steinberger Julia; Prineas Ronald J.; Sabin Matthew A.; Burgner David P.; Minn Heikki; Burns Trudy L.; et al. (SPRINGERNATURE, 2022)
Background: In high-income countries, cancer is the leading cause of death among middle-aged adults. Prospective data on the effects of childhood risk exposures on subsequent cancer mortality are scarce.
Methods: We examined whether childhood body mass index (BMI), blood pressure, glucose and lipid levels were associated with adult cancer mortality, using data from 21,012 children enrolled aged 3-19 years in seven prospective cohort studies from the U.S., Australia, and Finland that have followed participants from childhood into adulthood. Cancer mortality (cancer as a primary or secondary cause of death) was captured using registries.
Results: 354 cancer deaths occurred over the follow-up. In age-, sex, and cohort-adjusted analyses, childhood BMI (Hazard ratio [HR], 1.13; 95% confidence interval [CI] 1.03-1.24 per 1-SD increase) and childhood glucose (HR 1.22; 95%CI 1.01-1.47 per 1-SD increase), were associated with subsequent cancer mortality. In a multivariable analysis adjusted for age, sex, cohort, and childhood measures of fasting glucose, total cholesterol, triglycerides, and systolic blood pressure, childhood BMI remained as an independent predictor of subsequent cancer mortality (HR, 1.24; 95%CI, 1.03-1.49). The association of childhood BMI and subsequent cancer mortality persisted after adjustment for adulthood BMI (HR for childhood BMI, 1.35; 95%CI 1.12-1.63).
Conclusions: Higher childhood BMI was independently associated with increased overall cancer mortality.